Professional training in nutrition in Central and Eastern Europe: current status and opportunities for capacity development. Issue 2 (27th February 2014) - Gurinović, Mirjana; Novaković, Romana; Šatalić, Zvonimir; Nikolić, Marina; Milešević, Jelena; Ranić, Marija; Glibetić, Marija
Abstract: Objective: To examine the availability of academic programmes in nutrition and identify nutrition training needs in Central and Eastern Europe (CEE). Design: A questionnaire with close-ended and open-ended questions was distributed to the members of the United Nations University Standing Committee on Nutrition, Regional Network for Capacity Development in Nutrition in CEE (NCDN CEE). Setting: Participants' responses to the questionnaire including the comments of their colleagues from home institutions were obtained in group discussions during NCDN CEE meetings in 2010–2013. Subjects: Sixteen CEE countries' experts and their colleagues from home institutions involved in NCDN CEE activities 2007–2013. Results: The responses were obtained from fourteen out of sixteen participating countries; five countries have established Bachelor, Master and PhD studies in nutrition (Croatia, Czech Republic, Poland, Slovak Republic and Slovenia), whereas in Latvia and Republic of Macedonia only Bachelor and Master studies are set up. Seven countries have no Bachelor, Master or PhD studies: Bosnia and Herzegovina, Bulgaria, Estonia, Lithuania, Montenegro, Romania and Serbia. Introduction to data analysis and Nutritional epidemiology are the most needed nutrition trainings that would increase working competence of nutritionists and nutrition-related professionals in CEE. Conclusions: Availability of academic programmes in nutrition in CEE countries is limited. Opportunities for improving the competence of existing and future nutrition-related professionals should be addressed at national and regional level; distance learning courses and creation of a regional centre for nutrition training were seen as opportunities for sustainable capacity development in nutrition in CEE.